2017
DOI: 10.5530/ijper.51.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroscopic Characterization of Metal Complexes of Rosuvastatin

Abstract: Context: Rosuvastatin is a cholesterol lowering drug. It belongs to class statin. It is prescribed to the patients of coronary artery disease; atherosclerosis; thrombosis; increased low-density-lipoprotein; lipid and triglyceride. Aims:It is a newer drug in market and studies over the pharmacodynamics and pharmacokinetics are in progress. Statin therapy is a long term treatment for which its behavior in the presence of other agents is necessary. For this purpose present study is based on the interaction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results of the present study revealed that metformin and rosuvastatin decreased the levels of TBARS with an increase in the levels of GSH and thus demonstrated a significant in-vitro antioxidant effect with a possible beneficial effect in SCD. The antioxidant effects of metformin and rosuvastatin could be attributed to direct free radical scavenging activities, particularly hydroxyl radicals 17,18 , or to binding ability with metals like iron and copper 19,20 . H 2 O 2 in the presence of metal ions can be broken down rapidly leading to the generation of hydroxyl radical which may in turn initiate membrane lipid peroxidation 2 .…”
Section: Fig 1: the Effect Of Rosuvastatin Metformin On % Hemolysis (N = 15) C1 Control Group Of Rosuvastatinmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study revealed that metformin and rosuvastatin decreased the levels of TBARS with an increase in the levels of GSH and thus demonstrated a significant in-vitro antioxidant effect with a possible beneficial effect in SCD. The antioxidant effects of metformin and rosuvastatin could be attributed to direct free radical scavenging activities, particularly hydroxyl radicals 17,18 , or to binding ability with metals like iron and copper 19,20 . H 2 O 2 in the presence of metal ions can be broken down rapidly leading to the generation of hydroxyl radical which may in turn initiate membrane lipid peroxidation 2 .…”
Section: Fig 1: the Effect Of Rosuvastatin Metformin On % Hemolysis (N = 15) C1 Control Group Of Rosuvastatinmentioning
confidence: 99%
“…Metformin and rosuvastatin possibly chelate free iron released from erythrocytes hemolysis under oxidative conditions so decreasing its availability to generate ROS and membrane damage 2,19,20 . In an in-vitro study, Bai et al, 2013 21 , found that metformin can inhibit intracellular ROS generation through inhibiting NADPH oxidase enzyme which is present in high levels in sickle erythrocytes 3 .…”
Section: Fig 1: the Effect Of Rosuvastatin Metformin On % Hemolysis (N = 15) C1 Control Group Of Rosuvastatinmentioning
confidence: 99%
See 1 more Smart Citation